Multimedia multi-device educational presentations preserved as interactive multi-video objects - Viel, Caio César; Melo, Erick Lazaro; Pimentel, Maria da Graça Campos; Teixeira, César A. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
The capture of lectures or similar presentations is of interest for several reasons. From the attendee's perspective, students may use the recordings when working on homework assignments or preparing for exams, or to watch the contents of a missed class. From the instructor's perspective, a captured lecture may be evaluated, recaptured for improvements, or reused as complementary learning material. Moreover, captured lectures may be a valuable resource for e-learning and distance education courses. In this paper we detail the design rationale associated with the development of a prototype platform for the ubiquitous capture of live presentations and their transformation into a corresponding interactive multi-video object. Our approach includes capturing important context information which, when incorporated into the multimedia object, enables one to interact with the recorded lecture in novel dimensions. We tested our prototype by using case studies involving instructors and students, which allowed us to identify important features and novel uses for the platform.